Variation of parameters formulae with initial time difference for linear integrodifferential equations - Yakar, Coskun; Deo§, S. G. (Applicable analysis, 2006)
This article investigates the relationship between an unperturbed integrodifferential system and a perturbed integrodifferential system that have different initial positions and an initial time difference (ITD). Variation of parameter techniques are employed to obtain integral formulae and to define Lyapunov-like functions.